Crianças-bruxas da Nigéria – o filme de ficção ressignificando conceitos culturais - Segundo, Dátames Acastro Egg (2017)
This work aims at investigating a possible influence caused by Nigerian home-video productions, especially those made by Liberty Films, on the overall phenomenon of stigmatizing children accused of witchcraft, who consequently fall victim of abuse, abandon, torture and, quite often, death. We focus on the intersection of two growing and relatively new phenomena in Nigeria: the first one, the explosive growth of video productions in the country, which is nowadays considered the third biggest audiovisual producer in the world, rendering the national industry the nickname of Nolywood. The second, a recent re-signifying of terms and practices related to local religious culture, resulting in a surge in acts of violence against children accused of witchcraft. The term “witchcraft” frequently appears on movie titles produced every year in the country and is the main genre at Liberty Films, a well-known producer, specially in the south-center region of the country where the practices of stigmatization of children are more evident. Among the films launched by this producer, End of the Wicked deserves special attention once it approaches in a more straightforward manner the issue of children as vectors of witchcraft practices against their own families and acquaintances. The specific way in which the concepts of witchcraft were portrayed in the film, however, do not correspond to the known and documented social-historic meaning, highlighted in this research. The aim of this research is, therefore, to understand in which ways Nigerian films on the topic of witchcraft may be re-signifying such concepts and what is their influence on the accusations against children for witchcraft practices, specifically through the analysis of the film End of the Wicked.